Women, technology and gender-based violence in Bangladesh - Touhida Tasnima,; Md Azalanshah Md Syed,; Ruhana Padzil,; Siti Hajar Abu Bakar Ah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study gives an overview and critical analysis of the recent patterns, causes and consequences of Gender-Based Violence (GBV) in online spaces or through technological means in Bangladesh. In recent years, women in Bangladesh have become more exposed to violent stimuli as a result of the widespread use of smartphones and social media. Traditional ways of gender-based violence that took place offline have now transferred to the digital realm. This new trend of violence not only harms a woman physically, psychologically or socially but also restricts their freedom of movement, mobility, expression and opportunities in digital space. Moreover, the safety and privacy of women are at serious stake, where technological advancement has become one of the prime concerns for the government’s policy agenda for women's development and empowerment issues in Bangladesh. The study is based on qualitative content analysis and the empirical material consists of several number of newspaper reports written and published within the time frame of 2016 to 2022. The time frame was selected consciously to get the current scenario of the last six years. The study argues that inherent gender inequality and discrimination have a role in the consumption and use of technology to participate in the digital space and how this leads to violence against women in Bangladeshi society. This demonstrates how gender dynamics are generally patriarchal, which leads to online aggression.